Clinical Guideline for Nursing Care of Children with Head Trauma (HT): Study Protocol for a Sequential Exploratory Mixed-Method Study - Kord Z; Alimohammadi N; Jafari Mianaei S; Riazi A; Zarasvand B (Dove Medical Press, 2020)
Zeynab Kord,1 Nasrollah Alimohammadi,2 Soheila Jafari Mianaei,3 Ali Riazi,4 Behrooz Zarasvand5 1School of Nursing and Midwifery, Isfahan University of Medical Sciences, Isfahan, Iran; 2Critical Care Nursing Department, School of Nursing and Midwifery, Isfahan University of Medical Sciences, Isfahan, Iran; 3Children Care Nursing Department, School of Nursing and Midwifery, Isfahan University of Medical Sciences, Isfahan, Iran; 4Department of Neurosurgery, Isfahan University of Medical Sciences, Isfahan, Iran, Department of Pediatric Neurosurgery, Isfahan University of Medical Sciences, Isfahan, Iran; 5Department of Neurosurgery, Dezful University of Medical Sciences, Dezful, IranCorrespondence: Nasrollah AlimohammadiCritical Care Nursing Department, School of Nursing and Midwifery, Isfahan University of Medical Sciences, Isfahan, IranEmail alimohammadi@nm.mui.ac.irBackground: Head trauma is a major health problem. Its primary complications happen at the time of trauma and are inevitable; thus, head trauma management is focused on the prevention and management of secondary complications. A clear clinical guideline for head trauma care can help nurses effectively prevent and manage secondary complications. This study aims to develop the clinical guideline for nursing care of children under 18 years with head trauma hospitalized in emergency departments, critical care units, and neurosurgery wards.Methods: This sequential exploratory mixed-method study will be conducted in three main phases as follows: qualitative, systematic review, and integration phases. In the qualitative phase, semi-structured interviews will be conducted to determine the care-related needs of children with head trauma. In the systematic review phase, a systematic review will be performed to find and then to review the most relevant articles, books, and the appropriate clinical guidelines. The quality of the retrieved guidelines will be assessed using the Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument. In the integration phase, the findings of the qualitative and systematic review phases were integrated, the draft of the guideline will be prepared, which will then be revised and validated through a nationwide Delphi survey.Discussion: The guideline for nursing care of children with head trauma can help to more effectively prevent, reduce, and manage the secondary complications of head trauma. Moreover, it reduces disability and mortality rates, improves nursing care quality, decreases healthcare costs, shortens hospital stay, and makes more rational clinical decisions.Keywords: head trauma, nursing care, children, clinical guideline